2013
DOI: 10.1038/bjc.2013.251
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of CDKN2A hypermethylation in colorectal cancer: a meta-analysis

Abstract: Background:The prognostic value of CDKN2A promoter hypermethylation in colorectal cancer remains controversial. We systematically reviewed the evidence for assessment of CDKN2A methylation in colorectal cancer to elucidate this issue.Methods:Pubmed, Embase and ISI web of knowledge were searched to identify eligible studies to evaluate the association of CDKN2A hypermethylation and overall survival and clinicopathological features of colorectal cancer patients. Combined hazard ratios (HRs) or odds ratios (ORs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 28 publications
5
62
0
4
Order By: Relevance
“…In rectal cancer, Kohonen-Corish et al observed that CDKN2A methlytion occurred in 20% of patients, and that CDKN2A methlytion was associated with poor overall survival (13). CDKN2A hypermethylation is also associated with lymphovascular invasion, lymph node metastasis and proximal tumor location in colorectal cancer (14). In ovarian cancer, deletion of CDKN2A is also a common event (15).…”
Section: Discussionmentioning
confidence: 99%
“…In rectal cancer, Kohonen-Corish et al observed that CDKN2A methlytion occurred in 20% of patients, and that CDKN2A methlytion was associated with poor overall survival (13). CDKN2A hypermethylation is also associated with lymphovascular invasion, lymph node metastasis and proximal tumor location in colorectal cancer (14). In ovarian cancer, deletion of CDKN2A is also a common event (15).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the cell-cycle pathway have been described in multiple cancers (8)(9)(10)(11)(12) and are associated with poorer clinical outcome in some tumor types (13)(14)(15), including acute lymphoblastic leukemia (9), ovarian (10), colon cancer (12), and medulloblastoma (11).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CDKN2A promoter hypermethylation was shown to correlate with poor patient overall survival. 33 In juvenile myelomonocytic leukaemia (JMML), hypermethylation of CDKN2A was observed in 35% of the patients and correlated with poor outcome, 34 similarly to the patients diagnosed with non-small cell lung cancer Review Cancer Stem Cells (NSCLC), hypermethylation of p16 promoter was also associated with worse outcome. 35 The notion of slowing down the replication of cancer cells, a major hallmark of tumour biology, has been of great interest, and the efforts have escalated tremendously with the conceptualisation and discovery of cancer stem cells (CSCs).…”
Section: Polycomb Group Genes and Self-renewalmentioning
confidence: 99%
“…Furthermore, CDKN2A promoter hypermethylation was shown to correlate with poor patient overall survival. 33 In juvenile myelomonocytic leukaemia (JMML), hypermethylation of CDKN2A was observed in 35% of the patients and correlated with poor outcome, 34 similarly to the patients diagnosed with non-small cell lung cancer …”
mentioning
confidence: 99%